Women's experience of modernity, 1875-1945 - Lewis, Leslie W., 1960-; Ardis, Ann L., 1957- (Johns Hopkins University Press, 2003)
A contribution to feminist scholarship on the gender of modernism, challenging the assumption that modernism rose naturally or inevitably to the forefront of the cultural landscape at the turn of the 20th century. The book examines the writings of Jane Addams, Amy Levy, Rebecca West, and others.